Whose toilet is it anyway? : an ethnographic investigation into communally managed and municipally-managed janitor-serviced sanitation facilities in Masiphumelele, Cape Town - Schroeder, Matthew Wayne (Social Anthropology, 2016)
Informal settlement sanitation service delivery continues as one the most urgent, imposing challenges of contemporary basic service provision in South Africa. Municipal, provincial and national sanitation and political authorities expect informal settlement residents to take ownership of and responsibility for state-installed toilet facilities, with municipally-managed janitorial services also in operation in many settlements countrywide. Yet resident-driven sanitation management practices and the site-specific realities of informal settlements have not been adequately understood nor have they informed basic service delivery development. This has in part led to uncertainty in terms of how to designate and sustain responsibilities to relevant stakeholders regarding sanitation maintenance. Based on fieldwork in the Masiphumelele Wetlands informal settlement and temporary relocation area on Cape Town's southern peninsula, this dissertation describes a range of communally-managed sanitation systems that operate alongside municipally-managed janitorial services and which demonstrate varying degrees of local senses of ownership of responsibility for municipally-provided flush toilet facilities. A bottom-up, iterative development approach is argued for, one that critically considers the spectrum of factors that constrain and stimulate ownership and responsibility by informal settlement residents as well as the cultural contingencies that constitute communal sanitation management in informal settlements.